Medial Frontal Cortex in Action Monitoring - Luu, Phan; Flaisch, Tobias; Tucker, Don M (The Journal of neuroscience, 2000)
Effective behavior requires continuous action monitoring. Electrophysiological studies in both monkeys and humans have shown activity in the medial frontal cortex that reflects dynamic control and monitoring of behavioral acts. In humans, the centromedial frontal cortex shows an electrical response within 100 msec of an error, the error-related negativity (ERN). The ERN occurs only when subjects are aware of making an error, suggesting that a critical factor may be self-monitoring of the action process. In the present study, we examined late responses in a deadline reaction time task, in which the subject becomes increasingly aware of making an error as the response becomes increasingly late. We found evidence of response conflict before errors defined by late responses but not before errors defined by incorrect responses. The results also show a linear increase in the amplitude of the ERN with increasingly late responses. These data suggest that frontal networks provide dynamic representations that monitor and evaluate the unfolding action plan.